Strategies for becoming a more desirable mate: evidence from Lithuania - Apostolou, Menelaos; Sullman, Mark; Markšaitytė, Rasa; Šeibokaitė, Laura; Lajunen, Timo Juhani (Frontiers in Psychology, 2024)
Mate-seekers employ several strategies to become more attractive as mates. In the present study, we examined the use of 10 strategies for becoming more desirable as a mate in the Lithuanian cultural context. Using a sample of 295 Lithuanian-speaking participants, we found that the most frequently used strategy was "Enhance looks," followed by "Show off abilities and talents" and "Demonstrate similarity." The least used strategies were "Show off and exaggerate wealth" and "Drastic appearance changes." The 10 strategies could be classified into two domains or main strategies, with participants indicating a more frequent use of "Develop and demonstrate desirable traits" followed by "Deceive about undesirable traits." Sex differences and age differences were identified for several strategies.